the Relationship between Nursing Service Quality and Patient Satisfaction at Mulyorejo Community Health Center, Malang City, Indonesia - natarumanda, deva; Lilla Maria; Regista Trigandara (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
The quality of nursing services is crucial for a positive image of health service institutions. Patient satisfaction is a key indicator of the quality of nursing services. This study aims to analyze the relationship between nursing services and patient satisfaction at the Mulyorejo Community Health Center, Malang City. To analyze the relationship between nursing servic The quality of nursing services is crucial for a positive image of health service institutions. Patient satisfaction is a key indicator of the quality of nursing services. This study aims to analyze the relationship between nursing services and patient satisfaction at the Mulyorejo Community Health Center, Malang City.es and patient satisfaction at the Mulyorejo Community Health Center, Malang City. A correlational research design with a quantitative approach and a cross-sectional approach was used. Accidental sampling was employed to select a sample of 183 respondents from a population of 1,017 outpatients at the Mulyorejo Community Health Center between February and April 2023. Data were analyzed using the Spearman rank correlation test. The study found a strong positive correlation between nursing service quality and patient satisfaction. The quality of nursing services was rated as